Morphology and Evolution of the Xenarthra: an Introduction - Bargo, María Susana (2018)
This special issue of the Journal of Mammalian Evolution comprises a collection of articles presented at the symposium Morphology and Evolution of the Xenarthra^ organized and chaired by MSB and JAN. The symposium took place during the 11th International Congress of Vertebrate Morphology (ICVM-11), Washington, D.C., USA, from June 29 to July 3, 2016. The aim of the symposium was to bring together morphologists from around the world that work on extant and extinct xenarthrans, one of the most fascinating and enigmatic mammalian clades. Given the lack of an international conference that specializes on the group, there is a tradition of holding symposia that focus on the Xenarthra (X-symposia from here on) during the ICVM meetings. The past X-symposia took place in Jena (2001, ICVM-6), Paris (2007, ICVM-8), and Punta del Este (2010; ICVM-9).